Mosaic Orpheus - Scott, Peter Dale (Hugh MacLennan poetry series, 2009)
Working always to connect the polemical to the personal, Peter Dale Scott's political poems - from the tear gas of Berkeley protests in the 1960s to the problems of Thai forest monks in an era of drug-trafficking and deforestation - are a process of self-questioning. Self-questioning also marks his meditation poems, including a sequence on the death of his first wife. In opposition to contemporary poems of studied meaninglessness, Scott increasingly recognizes a compulsion in himself to radically reaffirm traditional rejections of the external world and turn to the refuges of poets before him, the enduring commonplaces that are more than cliches.